Internal structures of relative clause in Zarma - Waheed Ayisa Jayeola (Linguistik Online)
Although extensive works have been done on languages of the Nilo-Saharan family with generalizations made about the defining characteristics of their relative clauses, little can be said of this in relation to Zarma despite being a member language of the family. This paper investigates the features of Zarma relative clauses using the raising approach as well as some relevant aspects of the Minimalist Program (MP). Although, Zarma relative clauses are typologically postnominal, the study shows that the language employs discrete relative clause marker different from relative pronoun just as it uses gapping and resumptive pronoun strategies. Zarma relative clauses largely follow the universal pattern though relativisation in the language does not yield Subject object verb (SOV) ordering as assumed in some literature.